The Role of Live Streaming in Building Consumer Trust, Engagement, and Purchase Intention in Indonesian Social Commerce Thrift Clothes Sellers - Yasser, Amyra Salsabela; Gayatri, Gita (ASEAN Marketing Journal, 2023)
Manuscript type: Research Article Research Aims: Examine the relationship between shopping values consumers perceive during live streaming and their trust, engagement, and intention to purchase from Indonesian social commerce thrift clothes sellers. Design/methodology/approach: Data was gathered through an online survey from consumers who have watched a live-streaming session of an online thrift clothes shop on Instagram. Data were analysed using covariance-based Structural Equation Modelling (SEM). Research Findings: The output shows that only the utilitarian value of live stream positively affects trust in products and sellers. The variable engagement was only significantly affected by hedonic value. Additionally, the only significant indirect relationship is between utilitarian value and consumer engagement mediated by trust in products. Lastly, utilitarian value, symbolic value, and engagement positively affect the intention to purchase from Indonesian thrift clothes shops on Instagram, while hedonic value affects it negatively. Theoretical Contribution/Originality: This study extended several research models by utilising the Stimulus – Organism – Response framework to see how perceived values of live streaming on s-commerce affect consumer engagement and purchasing intention when mediated by consumer’s trust in the seller and product. Practitioner/Policy Implication: Marketers and entrepreneurs who sell thrift clothes on Instagram should utilise the Instagram Live feature while focusing on the utilitarian value to increase consumer engagement and intention to purchase. Research limitation/Implications: Demography, number of samples, and differences in live streaming style and thrift clothes brands still need to be addressed.